Cumulative Effect of Cascade Hydropower Development on Ecological Environment of Main Stream of Jinsha River - ZHOU Yang; YANG Jun (Renmin Zhujiang)
With the surge of human demand for water resources and the increasing socio-economic development, cascade hydropower development has become the main form of efficient utilization of water resources and hydropower development. Cascade hydropower development entails the construction of a series of reservoirs, which change the river form and material and energy transfer process, and have a cumulative effect on river and terrestrial ecosystems. Taking the cascade hydropower development in the main stream of the Jinsha River as an example, the cumulative effect of cascade hydropower development on the ecological environment is analyzed from hydrological, physicochemical, and ecological aspects. In the hydrological aspect, it is revealed that after dam construction, conspicuous runoff flattening, significant sediment interception, and water temperature stratification occur. In the physicochemical aspect, the physical form, water quality, and climate change characteristics of the river are discussed. In the ecological aspect, the process of how cascade dams affect fish and other aquatic organisms in the river is clarified. Based on these three aspects, a cumulative effect evaluation index system has been established on the spatio-temporal scale. Moreover, the possible eco-environmental problems led by cascade hydropower development are analyzed from different perspectives, which can provide a reference for the health assessment of hydropower development.